PUBLIC-PRIVATE PARTNERSHIPS FOR SUSTAINABLE URBAN DEVELOPMENT: LESSONS FROM INDONESIAN CITIES - Taufiqurrachman; Sari, Avid Leonardo; Irwandi; Pratomo, Soni; Indarti, Cynthia Febri Sri (Alqaprint Jatinangor, 2024)
Public-private partnerships (PPPs) have become an important strategy in sustainable urban development in Indonesia, especially amidst limited local government resources and challenges posed by rapid urbanization. While the private sector has great potential to provide financing and innovation, the success of PPPs depends largely on effective coordination between the public and private sectors. The dynamics of this relationship often face complex challenges, including equitable management of risks and benefits. This study aims to explore the factors that influence the success of PPPs in the context of sustainable urban development in Indonesia. This study uses a qualitative approach, with data obtained from various relevant previous studies and research. The collected data are systematically processed to find new patterns and insights related to PPPs. The results of this study indicate that strengthening the institutional capacity of local governments and increasing transparency and accountability are key to the success of PPPs. Private sector involvement not only provides financial resources but also brings significant innovation and efficiency. Inclusive collaboration, involving local communities and stakeholders, has proven to be essential to ensure the relevance and sustainability of PPP projects. In addition, supportive and adaptive policies to local conditions are needed to create a conducive environment for these partnerships. With the adoption of a comprehensive strategy, PPP can be an effective tool to achieve sustainable urban development goals in Indonesia.